Uji Model Alat Garuk Piringan dalam Mengendalikan Kentosan dan Berondolan Busuk di Perkebunan Kelapa Sawit - Sylvia Madusari; Rufinusta Sinuraya; Mubarok Ahmad (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
Research on the trial of modified scratching tools in the control of chitosan and rotten fruit in oil palm crop yielded in palm oil plantation PT. Fairco Agro Mandiri (PT FAM), Bukit Makmur Village, Kaliorang Subdistrict, East Kutai Regency, East Kalimantan Province, in May 2015. This research was conducted to find out the technique of controlling the chitosan and rotten fruit in the dish, there is an effectiveness and cost efficiency resulting from the treatment of the disk manually on the palm oil plant produces. The methods used in conducting this research are observation and modification of the scratching tool at the workshop, experimenting on field tools and evaluating the calibration of the modified rotary tool. Modified scratching tools in the control of chitosan and rotten fruit in palm oil produce better and more efficiently than scratching by using the scratching tools commonly used by workers. The use of this modified scratching tool can improve the performance of scratching from 5.36 hk / ha to 3.25 hk / ha (capir tool); 3.27 hk / ha (cepir tool 1); and 3.03 hk / ha (cepir tool 2). It can save the cost of scratching from Rp 907,984 to Rp 357,434 (capir tool); Rp 354.046 (cepir tool 1); and Rp 394,702 (cepir tool 2).